2020
DOI: 10.5334/aogh.2657
|View full text |Cite
|
Sign up to set email alerts
|

Caribbean Diaspora Healthy Nutrition Outreach Project (CDHNOP): A Qualitative and Quantitative Approach to Caribbean Health

Abstract: The Caribbean Diaspora Healthy Nutrition Outreach Project (CDHNOP) aims to improve the overall health and living experience of Caribbean immigrants and their families. The Caribbean diaspora population in the United States consists of individuals who are either born in the Caribbean or are of Caribbean descent and are currently living in the United States [1]. Despite the substantial proportion of Caribbean diaspora residing in the US, especially South Florida, there is a lack of representation in national dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Programs that are delivered in a clinical environment by a healthcare professional and center on patient self-management education are associated with a significant positive success rate with respect to patient HbA1c levels. This finding is meaningful and correlates with data from the parent CDHNOP study that showed most of the Caribbean focus group participants obtained health information from their doctor’s office(s) [ 2 ]. In contrast, features such as interventions focused on behavior-related tasks and delivery of the intervention at a participant’s home or by a nonhealthcare professional are shown to have less influence on patient HbA1c levels.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Programs that are delivered in a clinical environment by a healthcare professional and center on patient self-management education are associated with a significant positive success rate with respect to patient HbA1c levels. This finding is meaningful and correlates with data from the parent CDHNOP study that showed most of the Caribbean focus group participants obtained health information from their doctor’s office(s) [ 2 ]. In contrast, features such as interventions focused on behavior-related tasks and delivery of the intervention at a participant’s home or by a nonhealthcare professional are shown to have less influence on patient HbA1c levels.…”
Section: Discussionsupporting
confidence: 80%
“…Culturally sensitive interventions, defined in literature as processes that incorporate a specific population’s culture (e.g., norms, beliefs, values, and language), can be useful for addressing the needs of the Caribbean diaspora [ 1 ]. This scoping review is a derivative of the Caribbean Diaspora Healthy Nutrition Outreach Project (CDHNOP) research and community health initiative, which strives to improve health outcomes and reduce health disparities amongst Caribbean immigrants and their families in the US [ 2 ]. The Caribbean diaspora in the United States is a very diverse population made up of people originally from the Caribbean region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing these populations with culturally tailored education on the importance of a healthier lifestyle and shaping these dietary recommendations to fit their cultural norms could potentially ameliorate the rates of T2DM. The Caribbean Diaspora Healthy Nutrition Outreach Project demonstrated that providing populations with culturally tailored nutrition education was effective at changing their food and beverage selection, specifically in Cuban and Dominican communities [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…These disparities underline the importance of understanding the cultural considerations of T2DM in Latinx communities, including risk factors and access to care. This commentary with a modified scoping review aims to build off the existing “Caribbean Diaspora Healthy Nutrition Outreach Project (CDHNOP): A Qualitative and Quantitative Approach to Caribbean Health” [ 9 ] by further exploring the current data available on the Latinx community related to T2DM and its associated comorbidities. This manuscript is meant to provide a general overview of the literature available on these topics and discuss the need for a more inclusive, personalized, and comprehensive approach to improving the health of Latinx communities.…”
Section: Introductionmentioning
confidence: 99%